Perlindungan Hukum Pekerja Rumah Tangga dalam Hubungan Kerja Penuh Waktu - Luh Eni Pribadi; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Interpretasi Hukum, 2020)
A household assistant is someone who has basic duties and functions such as washing, cooking, cleaning the house, caring for the employer's child and various other tasks assigned by the employer. This study aims to analyze the form of legal protection of domestic workers in full-time employment relationships and find out the role of the Domestic Workers Distribution Agency in Full-time Work Relationships according to the Republic of Indonesia PERMENAKER No. 2 of 2015. The method used in this study is the normative method, sourced from primary and secondary legal materials. The results show that the form of legal protection for domestic workers has been set forth in the regulation of the Minister of Manpower Number 2 of 2015, as an effort to provide protection for domestic workers, to fulfill their rights as workers. Then, the role of the domestic worker supplier agency is as an intermediary to bring workers and employers together, the institution has the obligation to select prospective employers so that domestic workers do not fall into the wrong hands, the institution must also examine workers whether the workers are good and honest people so that no party who is harmed. Through this research, it is hoped that the government, especially in the field of Manpower, will further socialize the Minister of Manpower Regulation No. 2 of 2015 so that there is no violence against domestic workers. In addition, in preventing the occurrence of undesirable things to domestic workers, the channeling institution should pay more attention to the workers who are being dispatched, be more in depth with the background and origin of the prospective employer, supervise domestic workers by asking how the situation is and how the employer treats Domestic workers both by telephone and mail.